Effect of Fruit-Infused Water (Combination of Apple, Banana and Lemon) on Blood Glucose in Young Men - Ali, Mohammad Arif; Mukarromah, Siti Baitul; Anggita, Gustiana Mega; Suraya, Fatona; Anam, Khoiril (Pakistan Journal of Nutrition, 2016)
The purpose of this study was to investigate the effect of fruit-infused water (FIW) on blood glucose (BG) in young men. This study was conducted from 06:00 a.m. until 12:00 p.m. Twenty-four young men (19-20 year old) were divided into three groups: (1) fasting-only (FO), (2) fasting-water (FW) and (3) fasting-fruit-infused water (FF). All subjects fasted for 12 h before receiving treatment (water or fruit-infused water). Blood glucose was measured a total of 9 times before treatment and every 15 min after administration of treatment for 2 h. Fasting blood glucose indicated no significant differences among the 3 experimental groups: FO (100 mg/dL), FW (98 mg/dL) and FF (98 mg/dL). Interestingly, at the first 15 min, fruit-infused water appeared to elevate blood glucose [FF (107 mg/dL), FW (98 mg/dL) and FO (97 mg/dL)]. At the second 15 min, the elevation of BG in FF group was still elevated (115 mg/dL) compared with FW (96 mg/dL) and FO group (100 mg/dL). However, at the third 15 min, this elevation dropped slightly [FF (105 mg/dL), FW (94 mg/dL), FO (99 mg/dL)]. Beyond 60 min, following water/FIW intake there was no significant differences among the three groups. Fruit-infused water is able to elevate blood glucose. The elevation of BG from intake of FIW is maintained for approximately 45 min.